Literatura infantil: contribuições para aquisição e desenvolvimento da linguagem oral das crianças bem-pequenas - Ferreira, Vanessa Leão Franchi (2021)
The central argument of this Master's thesis is as sooner the child is inserted in Reading practices, - establishing literary texts appropriated to their age as the core of the practice - greater their linguistic development and more efficient oral language acquisition. In this research we search as investigative path, bring Brazil’s official data on the illiteracy rate to emphasize the importance of public policies that promote books distribution for early childhood, as well as encouraging reading practice in nursery. The questions that guide the research are: Is it possible the children's books contribute to the early childhood language acquisition and development? What are the linguistic resources present in the selected children's books that help in the early childhood language acquisition and development? Can the books of the Programa Nacional do Livro e do Material Didático – Literário 2018 be considered appropriate - from the language acquisition perspective - for early childhood? The main hypothesis is that reading books for early childhood contribute significantly to the language acquisition and development through the use resources, such as, rhyme, onomatopoeia, repetitions, etc.; in addition, as a subsidiary hypothesis, is that the books chosen by the Programa Nacional do Livro e do Material Didático – Literário 2018 are appropriate for the early childhood, because them present many linguistic elements that contribute to the language acquisition and development. And the qualitative paradigm was used in this research. To understand how the process of child's oral language acquisition and development occurs, Paula Menyuk’s e R. L. Trask’s theories were explored. Moreover, we are also based on the theories of Jean Piaget and Lev Vigotski. For a brief history of children's literature and its assumptions, we are based on Cecília Meireles, Nelly Novaes Coelho and Regina Zilbermann. Finally, we studied the official documents about early childhood literacy education, according to the Base Nacional Comum Curricular and Programa Nacional do Livro e do Material Didático – Literário 2018 policies and we analyzed four books from the Institution's catalog, namely Cabe aqui na minha mão, Eu sou assim e vou te mostrar, E você? and Rimarinhas, according to the theoretical framework raised.